THU0187 Safety of Tofacitinib, An Oral Janus Kinase Inhibitor: Integrated Data Analysis from The Global Chronic Plaque Psoriasis Clinical Trials. (15th July 2016) - Langley, R.G.B.; Cohen, A.D.; Foley, P.; Griffiths, C.E.M.; Lebwohl, M.; Leonardi, C.; Winthrop, K.; Proulx, J.; Rottinghaus, S.T.; Wolk, R.; Thompson, J.R.; Tatulych, S.; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis that is being investigated for psoriasis. Objectives: To report pooled trial safety data in patients with psoriasis to expand knowledge around the safety profile of tofacitinib in inflammatory diseases. Methods: The 1-year randomised controlled trials (RCT) group included patients with psoriasis who received ≥1 dose of tofacitinib 5 or 10 mg BID in three 1-year Phase 3 RCTs. The integrated safety group included patients with psoriasis who received ≥1 dose of tofacitinib in four Phase 3 studies (5 or 10 mg BID) or a long-term extension (LTE) study. In the LTE study, patients entered following one Phase 2 study or the Phase 3 studies and received 10 mg BID (for 3 months), then 5 or 10 mg BID (ongoing, database not locked, data cut-off April 4, 2014). Incidence rates (IR; patients with events/100 patient-years) were calculated for the 1-year RCT and integrated safety groups. For the integrated safety group, data were pooled across doses. Results: In the 1-year RCT group, 2436 patients received tofacitinib (5 mg BID, n=1217; 10 mg BID, n=1219), with a median of 253 days of tofacitinib exposure (range: 1–431, first and third quartiles: 168, 364). In the integrated safety group, 3623 patients received tofacitinib, with a median of 527 days of tofacitinib exposure (range: 1–1344, first and third quartiles: 261, 766). Serious infection IRs were 1.37 and 2.42 respectively for 5 and 10 mg BID in the 1-year RCT group, and 1.68 in the integrated safety group. Herpes zoster IRs were 1.00 and 2.32 for 5 and 10 mg BID in the 1-year RCT group, and 2.55 in the integrated safety group. Malignancy (excluding non-melanoma skin cancer [NMSC]) IRs were 1.12 and 0.81 for 5 and 10 mg BID in the 1-year RCT group, and 1.00 in the integrated safety group. NMSC IRs were 0.63 and 1.27 for 5 and 10 mg BID in the 1-year RCT group, and 0.74 in the integrated safety group. Major adverse cardiovascular event IRs were 0.50 and 0.23 for 5 and 10 mg BID in the 1-year RCT group, and 0.37 in the integrated safety group. In the 1-year RCT group, 95% confidence intervals for 10 vs 5 mg BID hazard ratios included 1 for each of these events. Conclusions: Serious infection, herpes zoster and NMSC IRs were numerically, but not statistically, higher with 10 vs 5 mg BID. IRs were similar in the RCT group and the integrated safety group, indicating that IRs are stable over time. Tofacitinib was well tolerated in patients with plaque psoriasis – including up to 44 months of exposure for some patients in the ongoing LTE study at data cut-off. Acknowledgement: Previously presented (Langley R et al. J Invest Dermatol 2015; 135 (S3): 39). This study was funded by Pfizer Inc. Editorial support was provided by Complete Medical Communications, and funded by Pfizer Inc. Disclosure of Interest: R. G. Langley Grant/research support from: AbbVie, Amgen, Celgene, Leo, Eli Lilly, Merck, Novartis, Pfizer Inc, Consultant for: AbbVie, Amgen, Celgene, Leo, Eli Lilly, Merck, Novartis, Pfizer Inc, Speakers bureau: AbbVie, Amgen, Celgene, Leo, Merck, Novartis, Pfizer Inc, A. Cohen Grant/research support from: Novartis, AbbVie, Consultant for: Pfizer Inc, Novartis, AbbVie, Janssen, P. Foley Grant/research support from: Galderma, Leo/Peplin, Ascent, Abbott/AbbVie, Janssen-Cilag, Wyeth/Pfizer Inc, Novartis, Roche, Consultant for: Galderma, Leo/Peplin, Ascent, Clinuvel, Janssen-Cilag, Eli Lilly, Australian Ultraviolet Services, Roche, Speakers bureau: CSL, Galderma, 3M/iNova/Valeant, Leo/Peplin, Ascent, Clinuvel, GSK/Stiefel, Abbott/AbbVie, Biogen Idec, Janssen-Cilag, Merck Serono, Schering-Plough/MSD, Wyeth/Pfizer Inc, Amgen, Novartis, Eli Lilly, Celgene, Roche, Aspen, BMS, C. E. Griffiths Grant/research support from: AbbVie, Actelion, Biotest, Celgene, Eli Lilly, Incyte, Janssen, Leo, MSD, Novartis, Pfizer Inc, Sandoz, Stiefel U.K., Trident, Zymogenetics and UCB, M. Lebwohl Consultant for: AbGenomics, Amgen, Anacor, Canfite Biopharma, Celgene, Clinuvel, Coronado Biosciences, Dermipsor, Ferndale, Lilly, Janssen Biotech, Leo, Merz, Novartis, Pfizer Inc, C. Leonardi Grant/research support from: AbbVie, Amgen, Anacor, Celgene, Coherus, Eli Lilly, Galderma, Janssen, Merck, Pfizer Inc, Sandoz, Stiefel, Leo, Novartis and Tolmar, Consultant for: AbbVie, Amgen, Dermira, Janssen, Boehringer-Ingleheim, Eli Lilly, Leo, Sandoz, UCB and Pfizer Inc, Speakers bureau: AbbVie, K. Winthrop Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, J. Proulx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Rottinghaus Shareholder of: Pfizer Inc, Employee of: Pfizer Inc (at the time of analysis), R. Wolk Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Thompson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Tatulych Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Mallbris Shareholder of: Pfizer Inc, Employee of: Pfizer Inc (at the time of analysis), R. Swanson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc